Coulomb correlations of a few body system of spatially separated charges (2009)
ABSTRACT: Hartree-Fock and Hartree-Fock-Bogoliubov study of a few body system of spatially separated charge carriers was carried out. Using these variational states, we compute an approximation to the correlation energy of a finite system of electron-hole pairs. This energy is shown as a function of the Coulomb coupling and the interplane distance. We discuss how the correlation energy can be used to theoretically determine the formation of indirect excitons in semiconductors which is relevant for collective phenomena such as Bose-Einstein condensation (BEC).